Validation of the PL-C Quest in China: understanding the pictorial physical literacy self-report scale - Wu, Yu; Wang, Xinxiang; Wang, Hongbiao; Wang, Lijuan; Tian, Ying; Ji, Zhiguang; Wang, Liyan (Frontiers in Psychology, 2024)
The notion of physical literacy is gaining interest from several countries as a potential mechanism for understanding the development of the physical self. This research endeavor represents an inaugural attempt to translate the Australian Physical Literacy Questionnaire for Children (PL-C Quest) into Chinese to evaluate the reliability and validity of the Chinese version of the PL-C Quest to assess physical literacy among children in mainland China. The Beaton translation paradigm was used to carry out language translation, back-translation, cultural adaptation, and presurveys. Data were collected from 642 children aged 6-12 years, with a mean age of 9.71 years (SD 1.816), to test the reliability of the Chinese version of the PL-C Quest. The PL-C Quest items translated well (6.187 15.499) and correlated well (0.441 0.622). The Chinese version of the PL-C Quest had good reliability, with retest reliability values ranging from 0.91 to 0.74, Cronbach's alpha from 0.65 to 0.894, and McDonald's ω from the Spearman-Brown Coefficient was 0.84. The validity results are acceptable because the CFI, IFI, and TLI values are above 0.8 and close to 0.9, but the model fit's chi-square degrees-of-freedom ratio of 2.299, the RMSEA of 0.05, which was less than 0.08. After translation and cultural adaptation, the Chinese version of the PL-C Quest is a reliable measurement tool and can be used in the Chinese region.